Reservoir properties and hydrocarbon enrichment law of Chang 1 oil layer group in Yanchang Formation, Wanhua area, Ordos Basin - Ji, Chaohui; Xue, Chengwei; Sun, Min; Li, Xiang; Wang, Li (Frontiers in Earth Science, 2023)
The evaluation of tight oil reservoir properties is of great significance to the exploration of tight oil and gas. In this study, the reservoir characteristics of the Chang 1 Member in the Wanhua area and the effects of superimposed sand bodies, structures and paleogeomorphology on hydrocarbon accumulation were systematically studied. The results show that the Chang 1 sandstone is a typical low-porosity and low-permeability reservoir, which has experienced destructive diagenesis such as mechanical compaction, pressure solution and cementation, and has experienced constructive diagenesis such as dissolution. The strong pressure solution caused secondary enlargement of quartz and feldspar and the formation of patchy dense mosaic structures. The cementation experienced by the target layer includes argillaceous, siliceous and carbonate cementation. Moreover, the sandstone reservoir in the Chang 1 Member also experienced strong dissolution, and dissolution is the main factor for the formation of secondary pores and the improvement of reservoir physical properties. The study also found that the main types of pores in the Chang 1 Member are intergranular dissolved pores and remaining intergranular pores. Superimposed sand bodies, nose-shaped uplifts, dominant facies areas and eroded paleo-highlands have significant effects on hydrocarbon accumulation. Based on this study, it is believed that the hydrocarbon migration and accumulation mode of the Chang 1 reservoir belongs to the ladder-like climbing migration + structural ridge accumulation type. In addition, sand body thickness is an important controlling factor for hydrocarbon accumulation. At present, the discovered crude oil in the Chang 1 Member is distributed in the areas with thick sand bodies (>20 m), and most of the sand bodies have a thickness in the range of 25-40 m, and the corresponding effective thickness is in the range of 2-6 m. In addition, the eroded highlands are the highest topographic units, which are favorable for the large-scale accumulation of oil and gas.